Merdeka Belajar in Islamic Education on Ahmadiyya Students' Perspective - Maimun; Azkar, Muh.; Ridwan; Wardi, Moh. (Al-Hayat: Journal of Islamic Education, 2025)
Ahmadiyya students represent a minority group within an educational setting dominated by the Sunni majority. This article explores their interpretation of freedom to learn in the context of Islamic Religious Education, which is largely shaped by the prevailing Sunni ideology encountered in classrooms and schools. The study employs a qualitative approach using a phenomenological method. Nine students from SMPN 16 Mataram were selected as informants. Based on in-depth interviews and observations, the findings reveal that Ahmadiyya students generally feel they are treated equally to other students and do not experience institutional discrimination. Nevertheless, they occasionally face negative treatment from peers. Despite the absence of overt discrimination, these students do not experience full educational freedom. The content of Islamic Religious Education often contradicts Ahmadiyya theological perspectives, particularly concerning the prophethood of Muhammad, Jesus, and Mirza Ghulam Ahmad. Additionally, they face challenges in participating in congregational prayers held in the school’s mushalla, as their doctrine stipulates that such prayers should ideally only be conducted with fellow Ahmadiyya adherents in Ahmadiyya mosques. Their compliance with school practices is largely a strategy to adapt, maintain personal safety, and avoid conflict, ridicule, or acts of aggression. This study has certain limitations due to the limited availability of research subjects to junior high school students, whose ability to provide in-depth responses is constrained. The originality of this research lies in its exploration of Ahmadiyya students' self-conception and their interpretation of freedom to learn within Islamic Religious Education in a school environment dominated by the Sunni majority.